Influence of Vertical Straightener Roller Shape on Residual Stress Level in Railway Rails - D. Woźniak; S. Żak (Archives of Metallurgy and Materials, 2024)
The required rail straightness is achieved by straightening with roller straighteners. The consequence of the straightening operation is the introduction of residual stresses to the straightened rail. An excessive level of residual stresses accumulated in the rail during use in the track may lead to its damage or fracture. ArcelorMittal Poland S.A., in cooperation with Łukasiewicz Research Network – Institute for Ferrous Metallurgy, carried out a research project (POI R.01.02.00-00-0167/16) the aim of which was to reduce residual stresses in railway rails by changing the technological parameters of the straightening process. The results of the presented study relate to rails 60E1 and 60E2. The study includes the measurement, testing, calculations and analyses of the obtained results. The conducted research indicates the possibility of obtaining a low level of residual stress in the rails for a system consisting of a 7-roller vertical straightener and a 9-roller horizontal straightener by changing the roller settings, the shape of the rollers, the shape of the rail foot and its curvature.